ADDRESSING EMPLOYEE TURNOVER IN THE LEBANESE RETAIL SECTOR: FACTORS AND SOLUTIONS - Khodor Shatila; Marina Alozian (Journal of Allied Research in Management and Entrepreneurship (JARME), 2023)
The Lebanese retail sector has been facing a decline in performance, attributed to high employee turnover caused by factors such as lack of motivation, engagement, and compensation benefits. This study aims to identify the factors behind employee turnover and find solutions to address it. Quantitative methodology was used in the form of distributing a questionnaire to a defined number of respondents from Lebanese retail companies. The study found that training and development, commitment, and loyalty tend to affect employee turnover. The literature review highlighted the relationship between effective leadership, communication, and performance in organizations, emphasizing the importance of employee engagement, motivation, and productivity.The study recommends change management and strategic planning to improve employee retention and decrease turnover in the Lebanese retail sector. Employee engagement, commitment, and training and development programs should be implemented to address factors leading to high turnover rates. The importance of effective leadership and communication in the workplace should also be emphasized. The study calls for a combination of quantitative and qualitative methodologies in larger case studies to provide accurate and comprehensive data for future research.